Environmental Policy and Investment Location: The Risk of Carbon Leakage in the EU ETS - Filippo Maria D'Arcangelo; Marzio Galeotti (Fondazione Eni Enrico Mattei (FEEM), 2022)
This paper empirically investigates the effect of the European Emission Trading Scheme (EU ETS) on cross-country investments. To avoid carbon leakage, the scheme allocates a number of free allowances to firms at risk of relocating investments in areas outside the EU ETS. To study this problem, we employ a model of the firm's investment decision in conjunction with novel firm-level data. In contrast with most previous literature, we stress the importance of firms' heterogeneity in the analysis and leverage it. We derive conditions for the firm's optimal emissions to construct a measure of investment sensitivity to carbon pricing from observed pollution data. This allows to identify the effect of the EU ETS on international investments by comparing the expected profits from investing in several different countries. We find that investments react to carbon pricing and that the effect is stronger for more polluting investments. However, the aggregate amount of diverted investments is small. We moreover show that the lost investments do not justify, alone, the generous compensations scheme aimed at retaining investments.
Keywords: D22; F18; Q52; Q54; 330; Emission trading; carbon leakage; investment location; EU ETS